2021
DOI: 10.1002/app.52062
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance fiber‐reinforced composites with a polydopamine/epoxy silane hydrolysis‐condensate bilayer on surface of ultra‐high molecular weight polyethylene fiber

Abstract: A bilayer structure with polydopamine (PDA) transition layer and 3-glycidyl ether oxy-propyl trimethoxy silane (GOPTS) hydrolysiscondensate strengthened layer on the surface of ultra-high molecular weight polyethylene (UHMWPE) fiber is prepared to improve the damage resistance of composites and more efficient stress transmission in composites. PDA is covered on the surface of UHMWPE fiber and then GOPTS is hydrolyzed and condensed to form inorganic -O-Si-O-with epoxy groups on the PDA layer. In addition, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The amino groups of the PDA layer could react with the epoxy groups of epoxy resin to form chemical bonds, thereby improving the interfacial bonding between fibers and resin. More epoxy block residues adhered on the surface of the UHMWPE fibers with chlorinated and following PDA deposition were found in Figure 9d, which indicated that the efficient dispersion of the stress in composites causes matrix resin to break into the small blocks attributing to the strong interfacial adhesion, and the fiber necking deformation was not widely observed because the stress transfer was interrupted between the short UHMWPE fibers with 5–8 mm in our composites, which was different form the stress transfer of fiber felts composites as the reported literature 28 …”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…The amino groups of the PDA layer could react with the epoxy groups of epoxy resin to form chemical bonds, thereby improving the interfacial bonding between fibers and resin. More epoxy block residues adhered on the surface of the UHMWPE fibers with chlorinated and following PDA deposition were found in Figure 9d, which indicated that the efficient dispersion of the stress in composites causes matrix resin to break into the small blocks attributing to the strong interfacial adhesion, and the fiber necking deformation was not widely observed because the stress transfer was interrupted between the short UHMWPE fibers with 5–8 mm in our composites, which was different form the stress transfer of fiber felts composites as the reported literature 28 …”
Section: Resultsmentioning
confidence: 55%
“…It showed that four characteristic peaks of 2917, 2848, 1472, and 717 cm −1 were attributed to methylene asymmetric stretching vibration, methylene symmetric stretching vibration, methylene asymmetric vibration and methylene in‐plane swing of UHMWPE, respectively 35 . For UHMWPE‐PDA fibers and UHMWPE‐Cl‐PDA fibers, the broad reflection bands around 3200–3600 cm −1 exhibited relatively stronger intensities compared with UHMWPE fibers and UHMWPE‐Cl fibers due to the asymmetric tensile vibration of OH and NH 28 from PDA deposited on the surface of UHMWPE fibers. While 1604 cm −1 was attributed to the CC stretching vibration of indole, suggesting that PDA had been successfully wrapped on the surface of the fibers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations